The value of sacral skin lesions in predicting occult spinal dysraphism in children with voiding dysfunction and normal neurological examination - ŞİMŞEK, FERRUH; ALPAY, HARİKA; TİNAY, İLKER; TARCAN, TUFAN (ELSEVIER SCI LTD, 2012)
Objective: The role of magnetic resonance imaging (MRI) in detecting occult spinal dysraphism (OSD) in children with voiding dysfunction and a normal neurological examination is still under debate. The aim of this study was to assess the correlation of sacral skin lesions with OSD detected on MRI, in a population of children with resistant lower urinary tract symptoms (LUTS). Patients and methods: A total of 114 children over 5 years of age with urinary tract infection (UTI) and/or LUTS and normal neurological examination were enrolled. All children underwent sacral neurological examination, urine analysis and cultures, renal/bladder ultrasound, voiding cystourethrogram and urodynamic examination. After a treatment period of 6 months, the patients were re-evaluated and spinal MRI was performed in 61 with ongoing LUTS or UTI. Results: Nineteen of 61 children (31%) had cutaneous stigmas. MRI detected spinal abnormality in 2/42 children with a normal sacral examination in comparison to 7/19 children with an abnormal sacral finding (Chi-squared test, P < 0.005). The sensitivity and specificity of an abnormal sacral finding in predicting MRI abnormality were 0.76 and 0.77, respectively. Urodynamic parameters did not predict an abnormal spinal MRI. Conclusions: Abnormal sacral findings, but not urodynamic studies, are strong predictors of OSD. A normal sacral examination does not rule out OSD. (C) 2010 Journal of Pediatric Urology Company. Published by Elsevier Ltd. All rights reserved.
Keywords: Sacral skin lesions; Occult spinal dysraphism; Voiding dysfunction; Spinal magnetic resonance imaging; BIFIDA; MARKERS